2019
DOI: 10.1111/jam.14223
|View full text |Cite
|
Sign up to set email alerts
|

Influence of culture conditions on the technological properties ofCarnobacterium maltaromaticumCNCM I‐3298 starters

Abstract: Aim The aim of this study is to investigate the effect of a broad spectrum of culture conditions on the acidification activity and viability of Carnobacterium maltaromaticum CNCM I‐3298, the main technological properties that determine the shelf‐life of biological time‐temperature integrator (TTI) labels. Methods and Results Cells were cultivated at different temperatures (20–37°C) and pH (6–9·5) according to a modified central composite design and harvested at increasing times up to 10 h of stationary phase. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 43 publications
(76 reference statements)
0
10
0
Order By: Relevance
“…The C. maltaromaticum strain was cultivated and frozen according to the procedure described by Girardeau et al [35], and the L. bulgaricus strains, according to the procedures described by Meneghel et al [2]. After centrifugation (Fig.…”
Section: Bacterial Strains Growth Conditions Freezing and Thawing Pro...mentioning
confidence: 99%
See 2 more Smart Citations
“…The C. maltaromaticum strain was cultivated and frozen according to the procedure described by Girardeau et al [35], and the L. bulgaricus strains, according to the procedures described by Meneghel et al [2]. After centrifugation (Fig.…”
Section: Bacterial Strains Growth Conditions Freezing and Thawing Pro...mentioning
confidence: 99%
“…To determine a potential effect of the protective conditions applied that differed between L bulgaricus [2] and C. maltaromaticum [35], the biological activity recovery of C. maltaromaticum was also investigated for cell pellets re-suspended in a sucrose solution (20 % wt in saline water) at a weight ratio of 1:2 and 1:1 (cell pellet weight: protective solution weight).…”
Section: Bacterial Strains Growth Conditions Freezing and Thawing Pro...mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it has been reported that high levels of some elements such as Mn 2+ , can improve biomass growth for some Carnobacterium spp. [ 43 , 44 ]. Acetic acid production was only observed at the initial batch fermentation (2.3 g/L), while no acetic acid production was observed after the pulse, probably due to the poor consumption of the remaining xylose.…”
Section: Resultsmentioning
confidence: 99%
“…Data used to calibrate and validate the model were partially reported in a previous study, in which a modified central composite experimental design was carried out to study the effect of operating conditions on the technological properties of C. maltaromaticum CNCM I-3298 [7]. Sixteen lab-scale fermentations (hereafter named F01 to F16) were performed using a wide range of regulated operating conditions (Figure 2): temperature between 20 and 37 • C and pH between 6.0 and 9.5. and trehalose, with similar growth rates.…”
Section: Methodsmentioning
confidence: 99%